Ethics Court as an Answer to the Need for Enforcement of Ethical Norms in a Modern Democratic System - Sapan, Heber Hombang; Santiago, Faisal (International Journal of Social Service and Research, 2025)
In a modern democratic system, the enforcement of ethical norms is a crucial aspect in maintaining the integrity and public trust in state institutions and strategic professions. However, there are still many ethical violations that are not handled adequately due to the limitations of existing legal mechanisms, especially when the violations are not categorized as criminal acts. Therefore, the urgency of establishing an Ethics Court is becoming increasingly relevant as a means to enforce moral standards, clarify the boundaries of professional behavior, and provide proportional sanctions for ethical violations. The Ethics Court can function as an independent institution that bridges legal norms and social norms, strengthens the internal oversight system, and encourages the creation of a culture of transparency and accountability. This study aims to analyze the concept, needs, and possibilities of implementing the Ethics Court in Indonesia by reviewing various comparative studies and applicable normative frameworks. It is expected that the results of this study can be an initial contribution to the discourse on the formation of effective and adaptive ethics institutions in the context of contemporary democracy.